Latex 2006 : Fourth International Conference on Latex and Latex Based Products : Frankfurt, Germany, 24-25 January 2006 - International conference on Latex and Latex based products (4th: 2006: Frankfurt, Germany); RAPRA Technology Ltd. (United Kingdom, UK : Rapra Technology Ltd., 2006)
22